Penentuan jenis mineral magnetik Guano dari Gua Solek dan Gua Rantai Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota menggunakan metode X-Ray Diffraction (Determination of the magnetic mineral type of Guano from Solek Cave and Chain Caves, Lareh Sago Halaban District, Lima Puluh Kota, using the X-Ray Diffraction method) - Dessupri Niarti; Hamdi Rifai; Fatni Mufit (PILLAR OF PHYSICS, 2013)
ABSTRACTFrom the result measurement of guano susceptibility magnetic, was found in Solek and Rantai cave indicate magnetic mineral. But the kinds of magnetic mineral it’s don’t know. The kinds of magnetic mineral consist of iron oxide and sulfide oxide. In this research will be determinate the kinds of magnetic mineral which from iron oxide use x-ray diffraction method. The guano which determinated from the kinds of magnetic mineral before extraction use strong magnet. Extraction process have function for desepared magnetic mineral and nonmagnetic mineral. The result from the extraction like smooth magnetic mineral and then will be measure use x-ray diffractometer. Based on the measure process with x-ray diffraction, know the kinds of magnetic mineral which indicate in guano of Solek and Rantai Cave at Lareh Sago Halaban District Lima Puluh Kota Regency, West Sumatera the most kind of mineral was magnetite 34). Then we also found another magnetic minerals such as hematite 23).Keywords: Guano, mineral magnetic properties, x-ray diffraction (XRD), iron oxide, sulfide oxide